Development of a tissue oxygen consumption measurement method based on near-infrared photoplethysmography - Nogawa, M.; Tanaka, S.; Shibata, M.; Yamakoshi, K. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2004)
A dual-wavelength reflectance optical oximeter sensor in combination with a simple photoplethysmographic technique was developed to measure the local tissue oxygen consumption from the simultaneous measurement of the arterio-venous oxygen saturation (SaO/sub 2/, SvO/sub 2/) differences, the physiological Fick principle. The performance of the reflectance oximeter was demonstrated in the theoretical simulation of the three-dimensional photon diffusion theory and the experimental study in the human subjects. As the results, the good agreements between theoretical and experimental studies of the oximeter were observed in the range of 70-100% SaO/sub 2/ and 70-90% SvO/sub 2/. The reflectance optical local tissue oxygen consumption measurement sensor would be applicable for various fields especially for the sports medicine, the patients monitoring and the transplanting organs monitoring.